2005
DOI: 10.1111/j.1365-2265.2005.02326.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of thyroxine replacement on the levels of serum asymmetric dimethylarginine (ADMA) and other biochemical cardiovascular risk markers in patients with subclinical hypothyroidism

Abstract: The present study demonstrated an elevation of hsCRP and ADMA plasma levels of patients with SH associated with a reduction in NO production, which may contribute to some cardiovascular alterations. The elevated ADMA and hsCRP levels were reduced after thyroxine replacement. Also the sdLDL levels of SH patients were found to be lower than the control group values whereas TC and LDL were elevated. Even though we found an elevation in sdLDL levels after treatment, those values were still not higher than in the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
34
4
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 29 publications
11
34
4
1
Order By: Relevance
“…Total cholesterol and LDL-C were significantly higher in patients with SCH as compared with control subjects, however triglyceride and HDL-C were not statistically different. The same results were obtained by Ozcan et al 2005 who reported high total cholesterol and LDL-C in patients with SCH [14]. Interestingly, they found reduced sdLDL levels in SCH patients.…”
Section: Discussionsupporting
confidence: 76%
“…Total cholesterol and LDL-C were significantly higher in patients with SCH as compared with control subjects, however triglyceride and HDL-C were not statistically different. The same results were obtained by Ozcan et al 2005 who reported high total cholesterol and LDL-C in patients with SCH [14]. Interestingly, they found reduced sdLDL levels in SCH patients.…”
Section: Discussionsupporting
confidence: 76%
“…[40] Several investigators have proposed ADMA as a potentially useful biomarker in cardiovascular disease. Until recently, there was no compelling evidence that ADMA plays a causal role in the pathophysiology of vascular disease.…”
Section: Discussionmentioning
confidence: 99%
“…One study investigated overt hypothyroid patients [7] and found no significant discordance in percentages of B phenotype (that represents predominance of sdLDL) from the controls. Another study on subclinical hypothyroidism [8] observed a decreased level of sdLDL in spite of raised TC and LDL-C. These two studies however did not adjust for the major confounding expected from triglyceride levels and hence we can not be sure that they truly reflect a hypothyroid effect.…”
mentioning
confidence: 99%